INFLUENCE OF STRUCTURAL DISPERSION AND COPPER CONTENTS ON FRICTION DURABILITY OF EUTECTIC ANTIFRICTION SILUMIN AK 15 - V. Ju. Stetsenko; A. I. Rivkin; K. N. Baranov (Литьë и металлургия)
It is shown that antifriction silumin with 15% silicon content has maximal frictional endurance in friction pair with steel at 3% copper content and dispersion of globular silicon crystals 3-4 micrometer.